The genus Haplopappus: botany, phytochemistry, traditional uses, and pharmacological properties - Mitsi, Christina; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Background: The genus Haplopappus Cass. [Asteraceae] comprises a large number of species distributed mainly in Chile and with various traditional medicinal uses. Purpose: The present review addresses the botany, traditional uses, chemistry, biological and pharmacological activities of the genus, aiming to further potentiate the associated research and applications. Study design and Methods: Literature data on the chemistry and bioactivity of the genus Haplopappus were mainly retrieved from digital databases such as SciFinder®, PubMed®, and Google Scholar®, as well as from the scientific journal publishers' platforms linked with these databases. Results and discussion: Although the majority of the botanical taxa of the genus Haplopappus has been understudied, available information is promising regarding its phytochemistry and bioactivity. A total of more than 400 compounds are present in different Haplopappus species, mostly terpenoids and phenolic compounds. Scientific literature supports various health promoting effects of Haplopappus extracts and isolated compounds, principally their effect against human pathogenic bacteria and their high antioxidant capacity. The existing limitations highlighted hereby are mainly associated to the lack of modern investigation regarding a wider number of Haplopappus species and chemical compounds, as well as to the absence of in vivo bioactivity results and clinical trials. Conclusion: Scientific literature supports the ethnopharmacological, phytochemical and bioactive potential of the genus Haplopappus, however the aforementioned limitations need to be addressed in order to further promote and broaden both scientific research and future applications and uses.